2021
DOI: 10.1021/acs.jmedchem.1c01305
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the First Potent IDO1/IDO2 Dual Inhibitors: A Promising Strategy for Cancer Immunotherapy

Abstract: Indoleamine 2,3-dioxygenase-1 (IDO1) plays an important role in tumor immune escape. However, unsatisfactory clinical efficacies of selective IDO1 inhibitors have impeded their further development, suggesting that they do not exert sufficient antitumor effects by selectively inhibiting IDO1. IDO2, an isoenzyme of IDO1, is overexpressed in some human tumors, and emerging evidence suggests that concomitant inhibition of IDO1/2 may have synergistic effects in cancer treatment, revealing a promising cancer immunot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 49 publications
0
18
0
1
Order By: Relevance
“…Compound 35 ( 4t ): Based on the crystal structures of Epacastat in complex with IDO1/2 and molecular modeling, He et al. 93 designed the first IDO1/IDO2 dual inhibitor ( 35 ) with IC 50 of 28.0 nmol/L and 144.0 nmol/L for IDO1 and IDO2, respectively. Compound 35 also blocked the kynurenine pathway with IC 50 of 2.2 nmol/L, and showed weak cytotoxicity.…”
Section: Small Molecule Immunomodulators Targeting the Tumor Microenv...mentioning
confidence: 99%
“…Compound 35 ( 4t ): Based on the crystal structures of Epacastat in complex with IDO1/2 and molecular modeling, He et al. 93 designed the first IDO1/IDO2 dual inhibitor ( 35 ) with IC 50 of 28.0 nmol/L and 144.0 nmol/L for IDO1 and IDO2, respectively. Compound 35 also blocked the kynurenine pathway with IC 50 of 2.2 nmol/L, and showed weak cytotoxicity.…”
Section: Small Molecule Immunomodulators Targeting the Tumor Microenv...mentioning
confidence: 99%
“…In CT26 xenograft mouse models, 4t showed a stronger anti-tumor effect than epacadostat. 96 Moreover, the antibiotic salinomycin was also reported to be a potent inhibitor of kynurenine synthesis, with IC 50 values of 3.36 μM, 4.13 μM and 4.66 μM in MCF-7, HeLa and MDA-MB-231, respectively, in a cell-based biochemical test. Mechanism studies revealed that salinomycin inhibits kynurenine synthesis mainly through suppressing IDO1 expression and its catalytic activity by blockade of JAK/ STAT and NF-κB pathways.…”
Section: Dovepressmentioning
confidence: 99%
“…If the pathogenic shift from early/mild to severe COVID-19 pneumonias is in part determined by the modulation of IDO1 and IDO2 expression in the pulmonary microenvironment as here hypothesized, the availability and selective use of specific IDO1 or IDO2 inhibitors might be crucial. A range of selective and potent TDO, IDO1, and IDO2 inhibitors are currently under investigation in cancer research and information from this field may be translationally utilized for new personalized therapies for patients suffering from COVID-19 and PACS [ 52 , 86 , 296 , 297 , 298 , 299 ].…”
Section: Introductionmentioning
confidence: 99%